2016
DOI: 10.3141/2589-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Needs of Road Maintenance in Sweden with the Mixed Proportional Hazards Model

Abstract: National road databases often lack important information for long-term maintenance planning of paved roads. In the Swedish case, latent variables of which there are no recordings in the pavement management systems database are, for example, underlying road construction, subsoil conditions, and amount of heavy traffic measured by the equivalent single-axle load. The mixed proportional hazards model with random effects was used to capture the effect of these latent variables on a road’s risk of needing maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This means that most sections reoccur several times in the data and the total carriageway length thus corresponds to more than today's total paved road network, which is approximately 84,000 km (52,000 mi). A previous study (19) found that the between-segment variation resulting from repeated observations was significant, that is, factors not included in the model affect the lifetime of individual road segments. However, these unobserved factors did not affect the parameter estimates, therefore, between-segment variation was not included in this study.…”
Section: Description Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This means that most sections reoccur several times in the data and the total carriageway length thus corresponds to more than today's total paved road network, which is approximately 84,000 km (52,000 mi). A previous study (19) found that the between-segment variation resulting from repeated observations was significant, that is, factors not included in the model affect the lifetime of individual road segments. However, these unobserved factors did not affect the parameter estimates, therefore, between-segment variation was not included in this study.…”
Section: Description Of Datamentioning
confidence: 99%
“…The survival models for estimation of expected lifetimes in this study were based on previous research using Swedish Pavement Management System data ( 17, 19, 24 ). The lifetime of a road is defined as the time between two maintenance treatments, where a maintenance treatment refers to a full-coverage repaving treatment on a more than 100-m-long continuous road section.…”
Section: Lifetime Analysismentioning
confidence: 99%